1987
DOI: 10.1111/j.1574-6968.1987.tb02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Histidine residues in Clostridium perfringens epsilon toxin

Abstract: Clostridium perfringens epsilon toxin was inactivated by ethoxyformic anhydride. A histidyl residue in the toxin was carbethoxylated under the conditions in which the toxin was completely inactivated, whereas tyrosyl residues were not affected. The toxin inactivated by ethoxyformic anhydride (EFA) was reactivated by treatment with hydroxylamine. These results indicated that a histidyl residue in the toxin is essential for its lethal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The epsilon toxin has been purified from some type D strains, and shown experimentally to increase vascular permeability in the brain [2], cause kidney damage [3] and contraction of the ileum [4], and to possess cardiovascular and pressor activities [5]. Little is known about the mode of action of epsilon toxin, and no enzymatic activity has yet been assigned to it, but the importance of certain amino acid residues for toxicity has been demonstrated [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The epsilon toxin has been purified from some type D strains, and shown experimentally to increase vascular permeability in the brain [2], cause kidney damage [3] and contraction of the ileum [4], and to possess cardiovascular and pressor activities [5]. Little is known about the mode of action of epsilon toxin, and no enzymatic activity has yet been assigned to it, but the importance of certain amino acid residues for toxicity has been demonstrated [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown that labeled toxin specifically accumulates in the brains of mice after intravenous injection and that the lethal activity of the toxin depends on its specific binding in the brain, probably to a sialoglycoprotein (28,29). Certain amino acids of epsilon-toxin, such as histidine, tryptophan, and aspartic or glutamic acid have been found to be essential for its biological activity (35)(36)(37)(38).…”
mentioning
confidence: 99%
“…Epsilon toxin was purified from epsilon prototoxin isolated from culture supernatants of C. perfringens type D (NCTC 8346), as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
“…We have reported that the toxin binding to mouse brain is essential to the lethal activity of the toxin (5) and that the toxin shows high affinity to brain and synaptosomal membranes (6), showing that the toxin is specifically bound to brain. We also have reported that one tryptophan (9,10), one tyrosine (11) and one histidine (12) residues in the toxin are important for the toxin binding to the brain (6). Recently, it was found that the toxin specifically stimulates dopamine release in rat brain (7), suggesting that the toxin activates dopamine nerve system in brain.…”
mentioning
confidence: 99%